Decolonising the curriculum to reinvigorate equity in higher education: A linguistic transformation - Lumadi, M.W. (South African Journal of Higher Education, 2021)
This article outlines the severity of historical injustices in the South African Higher Education system and introduces the key concepts that underpin the argument. Reporting on a series of interviews will be provided to demonstrate how these injustices continue to be perpetuated. “The subject of dissension” regarding “decolonisation” insinuates that the universities implicated in the study are colonial; “they are an integral part” of an empire that has a role in preserving fixed values for the wellbeing of an elite. This elite has the racial connotation of being white. Whiteness is an avenue for preserving their opulence and echelon within an ideological, theocratic capitalist modus operandi. This wrangle is disingenuous and ahistorical. Despite the revised language policy that seeks to promote multilingualism and facilitate inclusivity, social cohesion and meaningful participation by all students through focusing on previously marginalised languages, the associated institutions’ curricula, reproduce the community’s wider inequalities.